Regional Wage Differentiation and Wage Bargaining Systems in the EU - Vamvakidis, Athanasios (IMF Working Papers; Working Paper ;, 2008)
The theoretical literature has argued that a centralized wage bargaining system may result in low regional wage differentiation and high regional unemployment differentials. The empirical literature has found that centralized wage bargaining leads to lower wage inequality for different skills, industries and population groups, but has not investigated its impact on regional wage differentiation. Empirical evidence in this paper for EU regions for the period 1980-2000 suggests that countries with more coordinated wage bargaining systems have lower regional wage differentials, after controlling for regional productivity and unemployment differentials.